Giant cavernous aneurysm associated with trigeminal artery: treatment by detachable balloon. - Higashida, R T; Halbach, V V; Mehringer, C M; Hieshima, G B (American Journal of Neuroradiology, 1987)
300 Multiple ChoicesThis is a pdf-only article and there is no markup to show you.full-text.pdf